Body-Packer (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2024)
It is called body-parker, intracorporeal container or mules to the hidden ingestion of small packages of drugs of abuse such as cocaine or heroin, for illegal transportation, usually from one country to another. It was first described in 1973 by Dietel in a patient with intestinal obstruction who had ingested a condom containing drugs. The most common thing is that it presents asymptomatically in 90%, but it may occur that it presents complications (10%) such as obstruction, perforation or toxic complications in the case of rupture of the intraluminal capsule. The effective and usual diagnostic method is simple abdominal radiography (85 - 90% sensitivity and specificity) although ultrasonography and computed tomography can also be used.A patient who enters an asymptomatic third-level public hospital is brought up for discussion, brought by police officers, upon being found at an airport heading to Europe, detected by the refusal to be examined and nervousness about carrying out the interrogation. It is observed that he goes through all the steps that a person who carries drugs inside (body-packer) normally incurs from the airport where he was apprehended to the emergency hospitalization room, surgical observation, operating room, post-surgical hospitalization room and hospital discharge.
Keywords: Body packer; mule